Analysis of synthesized doped vertical silicon nanowire arrays for effective sensing of nitrogen dioxide: As gas sensors - Kashyap, Vikas; Pawar, Hariom; Kumar, Chandra; Chaudhary, Neeru; Saxena, Kapil (Frontiers in Materials, 2022)
In the present study controllably fabrication of Si NWs with vertical alignment is accomplished using metal assisted chemical etching (MACE). The different characteristics like structural, morphological, chemical, optical and dielectric properties have been analyzed using XRD, FESEM, Raman, UV-DRS and LCR meter. It has been analyzed from the morphological study i.e. from the FESEM that p type Si NWs are lesser in size than that of the n type Si NWs which attributes to the energy band gap. The optical band gap (Eg) is observed to increase from 1.64 to 1.89 eV with the decreasing in crystallite size, and the optical reflection spectra of the Si NWs show shift towards lower wavelength (blue shift). Moreover, Raman spectra has verified the red-shifted asymmetrically broadened Raman line-shapes, which provide information about the size confinement effect in Si NWs. The MACE approach is excellent for synthesizing nanowire structures for use in gas sensing applications due to its flexibility. The sensitivity of synthesized Si NWs has been tested towards NO2 gas. The sensor method presented here is noble and unique.